Polycystic ovary syndrome awareness among patients in a tertiary level teaching hospital: a questionnaire based observational study - Shaikh, Humera Gafur; Shah, Jui (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Polycystic Ovary Syndrome (PCOS) is a prevalent endocrine disorder affecting women of reproductive age. Despite its widespread occurrence, awareness remains inconsistent. This study aims to evaluate the awareness, knowledge, and perceptions of PCOS among participants, focusing on risk factors, symptoms, diagnostic modalities, treatment approaches, and sources of information. Methods: An observational study was conducted among women from diverse educational and occupational backgrounds. Data was collected through structured questionnaires assessing demographic details, awareness levels, knowledge of risk factors and symptoms, diagnostic approaches, treatment-seeking behaviour, and sources of information. Responses were analysed to identify trends, misconceptions, and gaps in knowledge. Results: The study showed that 40.6% of participants were aware of PCOS, a significant portion (39.6%) reported only partial awareness. The most commonly identified symptom was irregular periods (76.8%). A majority of participants (46.4%) were unsure about seeking medical treatment, reflecting hesitancy and misinformation. Management strategies such as lifestyle changes (32.9%) and medications (29.9%) were known to participants, but awareness of surgical options was low (4.3%). Notably, 30.4% of respondents relied on family and friends as their primary source of information, raising concerns about the accuracy of their knowledge. Conclusions: The findings highlight significant gaps in PCOS awareness, diagnosis, and management. Healthcare professionals play a crucial role in disseminating accurate information. Targeted educational interventions, enhanced healthcare communication, and community-based awareness programs are necessary to bridge knowledge gaps and promote early diagnosis and effective management of PCOS.